EFFECT MOIST WOUND HEALING TECHNIQUE TOWARD DIABETES MELLITUS PATIENTS WITH ULKUS DIABETIKUM IN DHOHO ROOM RSUD PROF Dr. SOEKANDAR MOJOSARI - Lutfi Wahyuni (Bahasa Indonesia, 2017)
Wound healing of ulkus diabetikum depends on wound treatment given; an appropriate wound treatment technique is able to help the healing process quickly and prevent amputation effectively. It needs wound treatment that is able to prevent advanced complication and increase wound healing process such as moist wound healing. This study aimed to aplicated technique with moist wound healing toward diabetes mellitus patients with ulcer diabetic in dhoho room RSUD Prof Dr. Soekandar Mojosari. Deskriptive explorative research design was used in this study. The number of sample were 20 respondents who were the whole ulcer diabetic patients on January – March 2016. The date were collected from the 1st and 7th wound treatment days of embroider medic and used observation sheets. The findings revealed that 20 respondents were on wound healing degree with regeneration wound; it means that the whole respondents cared by moist wound healing within 7 days got regeneration wound or net amelioration. Moist wound healing technique is able to keep moist of wound itself, so that it can facilitate cell and wound movement as well as expedite the granulation process about 50%. Therefore, after doing wound healing during 7 days, the significant change was on wound granulation development. Besides, it can minimize cell damage while the alteration bandage in order to prevent the new trauma and wound spread.